1979
DOI: 10.1021/es60150a006
|View full text |Cite
|
Sign up to set email alerts
|

Emissions from pressurized fluidized bed combustion processes

Abstract: Results of the comprehensive analysis of emissions from a pressurized fluidized-bed combustion unit (the Exxon Miniplant) are described as an illustration of the methodology for comprehensive analysis. The results are discussed in the context of the overall environmental assessment of the process being conducted by the U.S. Environmental Protection Agency. The comprehensive analysis of the fluidized-bed combustion emissions and process streams involved approximately 740 measurements on about 90 samples, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Anhydrite (CaSO 4 ) was the only identified solid product. The formation of anhydrite is in good agreement with the findings by Murthy et al,20 Ljungström and Lindqvist,21 Dam‐Johansen et al,16 and Tullin et al13…”
Section: Resultssupporting
confidence: 90%
“…Anhydrite (CaSO 4 ) was the only identified solid product. The formation of anhydrite is in good agreement with the findings by Murthy et al,20 Ljungström and Lindqvist,21 Dam‐Johansen et al,16 and Tullin et al13…”
Section: Resultssupporting
confidence: 90%
“…In accordance with the above remarks, the experimental evidence in most of the studies of the literature indicates strong effects of the pore size distribution on the overall reactivity of the calcined solids (Borgwardt and Harvey, 1972;Wen and Ishida, 1973;Coughlin, 1974, 1976;Ulerich et al, 1977;Vogel et al, 1977;Hasler et al, 1984;Simons and Garman, 1986;Yu, 1987;Gullett and Bruce, 1987;Zarkanitis and Sotirchos, 1989;Zarkanitis, 1991 desulfurization is known to occur in PFBC units (Bulewicz and Kandefer, 1986;Murthy et al, 1979 …”
Section: Background Informationsupporting
confidence: 52%
“…Analyses of gaseous and particulate emissions from a 0.08-m2 pressurized fluidizedbed combustor (PFBC) unit (Exxon Miniplant, N.J.) showed that SO, (0.18 lb/106 Btu) and NO, (0.09 lb/106 Btu) emissions were indeed below the limits of NSPS, but particulate emissions downstream of a 2cyclone collector were 2.75 g/m3 (1.9 lb/106 Btu), well above the NSPS requirement (Murthy et al, 1979). Fly ash characterization of flue gases from a 0.16-m2 atmospheric fluidized-bed combustor (AFBC) (Morgantown Energy Technology Center, Morgantown, W. Va.) using several different coals including Western Kentucky bituminous, Montana Rosebud subbituminous, and Texas Lignite has been reported (Newton et al, 1980;Carpenter et al, 1980;Hobbs and Carpenter, 1980).…”
Section: Introductionmentioning
confidence: 99%